TEORI KEADILAN DALAM PERSPEKTIF FILSAFAT HUKUM DAN ISLAM - Muhammad Kurniawan Budi Wibowo (Institut Islam Mamba'ul 'Ulum Surakarta, 2018)
The existence of Islamic law in the world is to regulate human life, both as a person and as a member of society in order to behave according to the wishes of the Creator. This is different from the general concept of law which is only intended to regulate human life as members of society or in other word the law exists because of the conflict of human interest. Among the problems in the philosophy of Islamic law, the most frequent discourse is about the issue of justice in relation to the law. This is because the law or regulation must be fair, but in fact it is often not. This paper will describe this issue of justice from the perspective of legal philosophy and Islam. In the perspective of legal philosophy, the author will only parse the theory of justice Aristotle and John Rawl. Whereas in the perspective of Islamic legal philosophy, the author will parse the theory of the Muktazilah and Asyariyah divine justice, and the Islamic Maqasyid Theory as the ideals of Islamic legal social justice.